Descriptive retrospective study on dental implant failure by analyzing various factors: a 15-year study - Khan, Abdullah Al Mamun; Zahan, Nasrin Parvin (International Journal of Research in Medical Sciences, 2025)
Background: Dental implant failure remains a significant clinical challenge despite advances in implantology. Understanding the underlying causes and contributing factors is crucial for improving implant success and patient outcomes. Methods: This descriptive retrospective study was conducted over 15 years from January 2010 to December 2024 at two specialized dental centers in Dhaka, Bangladesh Banasree Dental and Implant Center and German Dental and Implant Center. Clinical records of 261 patients, aged 20-90 years, who received a total of 510 implants were reviewed. Data were collected from clinical files, radiographs and follow-up records to evaluate implant characteristics, duration of survival and causes of failure. Results: Of the 261 patients, 158 (61%) were male and 103 (39%) were female, with a male-to-female ratio of 1.5:1. Most patients were middle-aged or older. A total of 285 implants (55.9%) were placed in the maxilla and 225 (44.1%) in the mandible. The majority (95.49%) received initial treatment at other clinics. Implant survival duration ranged from 6 months to 3 years. The primary causes of implant failure were infection (peri-implantitis) in 40.2%, improper placement in 25.3%, insufficient bone density in 17.2%, mechanical issues in 10.3%, systemic health issues in 5.7% and excessive stress in 1.1%. Failures were more frequent in the maxilla (58.2%) and occurred predominantly within the first year (41.4%). Conclusions: Infection and improper implant placement were the leading causes of dental implant failure, with higher risk observed in maxillary implants and early post-implantation periods. Rigorous surgical planning and follow-up are essential for minimizing failures.